Перформативный поворот в постсоветской культуре - Polishchuk, Yaroslav (Studia Rossica Posnaniensia, 2019)
The author of the article considers the elements of performance in the literary works of the post-Soviet period. His attention is focused on three East Slavic nations, whose literatures belonged to the area of “Soviet literature” for a long time. It is noted that the implementation of the elements of performance into the culture confirms the radical renewal of literary discourse and creation of new national narratives.